Circulating Biomarkers in Patients With Locally Advanced or Metastatic Renal Cell Carcinoma Treated With Everolimus in the Pre-nephrectomy Setting. Issue 3 (March 2023) - Mauge, L.; Phan, L.; Benhamouda, N.; Galy-Fauroux, I.; Badoual, C.; Topart, D.; Thiery-Vuillemin, A.; Le Moulec, S.; Guillot, A.; Cessot, A.; Mejean, A.; Albiges, L.; et al.
Abstract: Many drugs are available in renal cell carcinoma (RCC), yet clinicians are still looking for predictive biomarkers of disease recurrence or progression supporting more personalised treatments. An assessment of circulating biomarkers over time was carried out in this French, open-label, single-arm, multicentre trial conducted in 25 patients with either locally advanced ( n = 14) or metastatic RCC ( n = 11) who received everolimus (10 mg daily) for 6 weeks prior to nephrectomy (NEORAD, NCT01715935). Circulating biomarkers, including circulating tumour cells, haematopoietic and endothelial cells, plasma angiogenesis and inflammatory markers were quantified at baseline, upon everolimus and post-nephrectomy. We assessed tumour burden, objective response rate upon RECIST1.1, disease-free survival (DFS) and progression-free survival (PFS). The correlation between circulating biomarkers was evaluated with multiple factor analysis and biomarker association with DFS/PFS by Cox regression. No objective response rate was obtained before nephrectomy. Upon everolimus, neutrophils, platelets and sVEGFR2 significantly decreased. We did not find any association between circulating biomarkers and DFS/PFS, but patients with the highest tumour burden at baseline had significantly higher plasma levels of interleukin-6, an inflammatory circulating biomarker, and lower levels of sVEGFR2, related to angiogenesis. Further understanding of the link between these circulating biomarkers could help to optimise drug combinations in RCC. Highlights: Circulating biomarkers (CB) may predict outcomes in everolimus-treated RCC patients. IL-6 cytokine positive correlation to tumor burden may reflect inflammation. Soluble VEGFR 2 inverse correlation to tumor burden may reflect hypoxia. These CBs could be interesting for immunotherapy alone or combined to TKI. Abstract : Mercuric chloride; Vitamin E; Zinc chloride; Oxidative stress; Apoptosis.